Comparison of two immunochromatographic assays and the indirect immunofluorscence antibody test for diagnosis of Trypanosoma cruzi infection in dogs in south central Louisiana - Nieto, Prixia D.; Boughton, Roger; Dorn, Patricia L.; Steurer, Frank; Raychaudhuri, Syamal; Esfandiari, Javan; Goncalves, Edson [UNESP]; Diaz, James; Malone, John B. (Elsevier B.V., 2009)
Two rapid tests evaluated in dogs considered to be of high risk of Infection with the Chagas parasite Trypanosoma cruzi using two immunochromatographic assays. Trypanosoma Detect (TM) for canine, InBios, Seattle, WA and CHAGAS STAT-PAK (TM) assay, Chembio Diagnostic Systems, Medford, NY, in south central Louisiana. For this purpose a serological survey was carried out in a total of 122 dogs and a serum bank was created. These 122 animals were first tested by IFAT that was used as the standard test From the serum bank 50 samples were tested using the two rapid Chagas assays and results compared to the standard test IFAT The serological survey using IFAT showed it prevalence of T cruzi infection in 22.1% of the tested dogs. In the immunochromatographic assays. 13 and 11 animals were positive on rapid assay Trypanosoma Detect (TM) for canine, InBios and CHAGAS STAT-PAK (TM), Chembio Diagnostic Systems, respectively compared to 11 positive by IFAT. These two immunochromatographic tests have shown high susceptibility and specificity compared to our standard method IFAT. The rapid, easy and accurate screening assays used in conjunction with confirmatory tests, would be an excellent tool for veterinarians to diagnose T cruzi infection. Early detection of T cruzi infection may prevent complications through an effective treatment. Greater awareness by veterinarians of the risk. clinical findings, history along with diagnostic methods will contribute greatly to an understanding of the true prevalence of Chagas disease in dogs in Louisiana. (c) 2009 Elsevier B.V. All rights reserved.
Keywords: Chagas in dogs; Trypanosoma cruzi; Diagnosis; Zoonotic disease; American trypanosomiasis